Phenolic composition and antioxidant activity of Bursera microphylla A. Gray - Vidal-Gutierrez, Max [UNESP]; Robles-Zepeda, Ramon Enrique; Vilegas, Wagner [UNESP]; Gonzalez-Aguilar, Gustavo Adolfo; Torres-Moreno, Heriberto; Lopez-Romero, Julio Cesar (Elsevier B.V., 2020)
Bursera microphylla is an endemic plant from Sonora desert, used in folk medicine, however, there is a few scientific information about compounds profile and antioxidant activity. The objective of the study was to determine the phenolic profile and antioxidant activity of B. mycrophylla leaves (BMLE) and fruits (BMFE) extracts. Phenolic content was quantified by the Folin-Ciocalteu assay and phenolic compounds (PC) profile was investigated using UHPLC-ESI-IT-MS and ESI-IT-MSn analysis. Antioxidant activity was evaluated through the 1,1diphenyl-2-picrylhydrazyl (DPPH), trolox equivalent antioxidant capacity (TEAC), oxygen radical antioxidant capacity (ORAC) and ferric reducing antioxidant power (FRAP) methods. Obtained results showed that BMLE (243.4 mg GAE/g) presented higher amount (p < 0.05) of PC compared with BMFE (104.3 mg GAE/g). A total of 11 phenolic compounds were identified in the evaluated extracts (4 phenolic acids, 6 flavonols and 1 flavan-3ol). Antioxidant evaluation results evidenced that BMLE [DPPH IC50 (concentration to inhibit the 50% of DPPH radical): 34.7 mu g/mL; TEAC: 79.3 mu M TE/g; ORAC: 1632.8 mu M TE/g; FRAP: 3809.4 mu M Fe(II)/g] exhibited the greatest capacity (p < 0.05) to stabilize free radicals and reduce metals. Additionally, a strong correlation between antioxidant activity and PC (DPPH vs PC: r= 0.96; TEAC vs PC: r= 0.95; ORAC vs PC: r= 0.96; FRAP vs PC: r= 0.96) was observed. This study is the first one that report the antioxidant potential and phenolic profile of B. mycrophylla plant. In addition, B. mycrophylla extracts showed an interesting antioxidant potential, which could be considered as a natural source of antioxidant compounds.
Keywords: Bursera microphylla; Antioxidant; Phenolic compounds